2014
DOI: 10.13080/z-a.2014.101.041
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of seed fatty acid profile of pepper (Capsicum annuum L.) cultivars on germination at various temperatures

Abstract: The present study was undertaken to determine the fatty acid profile of seeds of pepper (Capsicum annuum L.) cultivars 'Yağ', 'Çetinel-150' and 'Bağcı Çarliston' as well as the relations between fatty acid profile, seed germination and vigour at various temperatures (15, 25 and 35 °C). In this study, the germination percentage and vigour, total oil and the fatty acid profile of seeds of pepper cultivars were determined. There were significant differences in seed germination and vigour among the cultivars. Lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…is catalyzed by LIPG to form fatty acids and glycerin; thereafter, fatty acids and glycerin are converted to sucrose via glycolysis, tricarboxylic acid cycle, or glyoxylate cycle, thereby providing nutrients for seed germination (Kaymak, 2014;Basnet et al, 2016). We confirmed that HDT significantly suppressed LIPG, ACX, and INV activities along with their associated gene expression in 12-month-stored sunflower seeds during the early germination stage.…”
Section: Hdt Inhibited Triacylglycerol Hydrolysis To Sugars In Stored Sunflower Seedssupporting
confidence: 65%
“…is catalyzed by LIPG to form fatty acids and glycerin; thereafter, fatty acids and glycerin are converted to sucrose via glycolysis, tricarboxylic acid cycle, or glyoxylate cycle, thereby providing nutrients for seed germination (Kaymak, 2014;Basnet et al, 2016). We confirmed that HDT significantly suppressed LIPG, ACX, and INV activities along with their associated gene expression in 12-month-stored sunflower seeds during the early germination stage.…”
Section: Hdt Inhibited Triacylglycerol Hydrolysis To Sugars In Stored Sunflower Seedssupporting
confidence: 65%
“…The pre-test with two temperatures showed that the highest seed germination percentage was achieved at 24°C and 28°C, because the pepper species seeds germinate well in a constant temperature range between 15°C and 30°C (Kaymak, 2014); however the highest germination rate of pepperoncini was …”
Section: Discussionmentioning
confidence: 98%
“…Specifically, limited information is available on the relationship between seed traits and fatty acids. In previous reports, the authors found that both seed germination and vigour are two vital seed traits that could be influenced by colour of seed and fatty acid content (Dogras et al 1977;Kaymak, 2012;Kaymak, 2014a;Kaymak, 2014b, Kaymak, 2015. The fatty acid content of the seed has been related to germination and seed vigour in different crops.…”
Section: Introductionmentioning
confidence: 98%